EVALUASI AIRTANAH UNTUK PENGEMBANGAN WILAYAH PANTAI. Kasus : Di Gumuk Pasir dan Dataran Aluvial Pantai Antara K. Opak dan K. Progo Propinsi Daerah Istimewa Yogyakarta (GROUNDWATER EVALUATION FOR THE DEVELOPMENT OF COASTA - Perpustakaan UGM, i-lib ([Yogyakarta] : SekolahPascasarjana Universitas GadjahMada, 2000)
ABSTRACT A sustainable groundwater resources management should be aimed to preserve groundwater resources and environmental qualities in the long term. The aim of this study was to evaluate groundwater in sand dunes and coastal alluvial plain for province development of coastal area in Yogyakarta Special Region (DIY). In order to attain the mentioned above, various information was needed, i.e. geology, hydrology, hydrogeology, social economic, and landuse. The result of this study showed that flow direction of groundwater was north south and the type as unconfined aquifer. Sand dunes has fine to medium sand grain and coastal alluvial plain has coarse sand to pebble grain. Static reserve at sand dunes 34,964,381.25 m3 to 40,034,3625 m3 and coastal alluvial plain 114,764,259.4 m3 to 125,616,740.6 m3. The total amount of groundwater establishment at sand dunesis 8,302,379.375 m3/year to 11,472,485.38 m3/year and coastal alluvial plain 14,794,605.63 m3/year to 16,872,958.63 m3/year. The amount of water used at sand dunes is 226,080.565 m3/ year and coastal alluvial plain 1,777,823.233 m3/year, so that this study has no critical point yet (critical value at sand dunes is 2,72 % and coastal alluvial plain 12,02 %). Zone of Groundwater development could be devided into three types, as a result of overlay method, namely : zone I, zone II, and zone M. Zone I could be used without barrier or with very light barrier. Zone II could be used with light barrier, and Zone III could be used with moderate barrier. In the sand dunes, in zone I the value was 22,54 %, zone II 60,7 %, and zone in 16,76 % from sand dunes area. In the coastal alluvial plain, in zone I the value was 86,28 %, and zone I113,72 % from coastal alluvial plain area. The result of the study showed that the landuse was suitable to domestic, plantation , agriculture, and industry.